MINAT REMAJA UNTUK MELANJUTKAN KE PERGURUAN TINGGI DI KECAMATAN PULO ACEH KABUPATEN ACEH BESAR - Firmawati Firmawati; Al Ikhsan (State Islamic University (UIN) Ar-Raniry, 2018)
This study aims to know the description of an interest in youth to continue to Higher Education in the District of Pulo Aceh, Aceh Besar District. This study uses a quantitative approach with descriptive method. The number of juvenile population in the District of Pulo Aceh amounted to 407 people with a total sample of 80 people based formula Slovin and using sampling technique called incidental sampling technique. Data collection techniques by observation, interviews and questionnaires. Previous questionnaires that have been tested by using validity and reliability. Data analysis technique used is Test Mean. The results generally show that 67.5% interest in youth to continue to Higher Education in the District of Pulo Aceh, Aceh Besar District is located in the lower category which means that most teenagers do not have the will or do not want to continue on to college. Teenagers trying to be independent and seek employment in order not to charge the parents, and it was thought sufficient to public high school just studying can already get a job. Teens mostly show their displeasure, lack of attraction to pursue higher education.